A Morphological Study of Building and Creating Of Theatre Sets Management in Istana Budaya - Musa Kahn, Sabzali (2008)
This thesis focuses on the morphological study of building and creating theatre sets in Istana Budaya. For the purpose of this study, qualitative method was used (interviews) in order to obtain in-depth and rich data. The result of this study shows that set designers and their production teams play vital roles in producing solid and high quality productions. Human resource factors, such as Cognitive Psychology and work support are among the important aspects that should be given serious attention in any given production of performances. It is found that production project supervision will not be effective if information conveyed is not communicated well to team members. Thus, set designers and their production teams should composed of various experts that can contribute in building and creating solid theater sets. Application methods, such as morphology and square drawing template, can be employed as effective means in the creating and building process for a performance production. More effort should be given to ensure that the performance production in general will continue to progress and to achieve success in the future. Hence, the expertise of set designers and their teams should be expanded to produce more professional and competent production community in the future.